Role of tumor-associated macrophages in hepatocellular carcinoma: impact, mechanism, and therapy - Zhang, Yinqi; Han, Guoyong; Gu, Jian; Chen, Zhiqiang; Wu, Jindao (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) is a highly frequent malignancy worldwide. The occurrence and progression of HCC is a complex process closely related to the polarization of tumor-associated macrophages (TAMs) in the tumor microenvironment (TME). The polarization of TAMs is affected by a variety of signaling pathways and surrounding cells. Evidence has shown that TAMs play a crucial role in HCC, through its interaction with other immune cells in the TME. This review summarizes the origin and phenotypic polarization of TAMs, their potential impacts on HCC, and their mechanisms and potential targets for HCC immunotherapy.